Exploring Organizational Health to Achieve Organizational Agility - Kismono, Gugup; Danarilia, Vania Olivine; Ardianto, Heni (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
Organizational health is crucial for influencing effectiveness, ethics, culture, and decision-making. Initially focused on employee treatment, organizational health now emphasizes a balance of stability and flexibility in structure, governance, and processes. The Organizational Health Index (OHI) evaluates organizational health across nine dimensions, highlighting leadership, continuous improvement, talent development, and market creation. Analysis shows that the Office of Kampus Merdeka (Pelaksana Pusat Kampus Merdeka/PPKM) is in the top quartile for agility and adaptability, confirming that a healthy organization is innovative and responsive. Institutional theory supports that organizational health fosters a productive and adaptive work environment. Integrating organizational health principles in institutions like PPKM through programs like Merdeka Belajar Kampus Merdeka (MBKM) is vital for academic and industrial growth, demonstrating the link between organizational health and employee well-being.